Piedmont deposits as seismic energy dissipators, Sierras Pampeanas of Argentina - Gutierrez, Adolfo Antonio (2021)
This study shows the neotectonic deformation occurred in the southern piedmont of the Cumbres Calchaquíes, in the Amaicha and Tafí valleys. Neotectonic deformation manifests itself through faults, folds and diversions of drainage channels. The Amaicha valley is bounded to the north by the Tafí del Valle fault and to the south by the Los Cardones fault. The Cumbres Calchaquíes ride over the Sierra de Aconquija through the Los Cardones and Carapunco faults. The Carapunco fault also has a synestral component, responsible for generating an imbricated system of contractional fractures. In the study region many earthquakes of ≥ 3 and ≥ 4 magnitude coincide with regional faults evidencing its neotectonic activity. The seismic energy dissipated through materials with less cohesion that form the fill of the valleys, generating discrete fault scarps and strongly folded conglomerate strata. The foothills deposits of the Cumbres Calchaquíes absorbed most of the seismic energy released during the reactivation of the faults. Tectonic activity is deforming 630 a BP deposits in the Cumbres Calchaquíes piedmont.